Intraoperative Hemi-Diaphragm Electrical Stimulation Demonstrates Attenuated Mitochondrial Function without Change in Oxidative Stress in Cardiothoracic Surgery Patients - Robert T. Mankowski; Stephanie E. Wohlgemuth; Guilherme Bresciani; A. Daniel Martin; George Arnaoutakis; Tomas Martin; Eric Jeng; Leonardo Ferreira; Tiago Machuca; Mindaugas Rackauskas; Ashley J. Smuder; Thomas Beaver; et al. (MDPI AG, 2023)
Mechanical ventilation during cardiothoracic surgery is life-saving but can lead to ventilator-induced diaphragm dysfunction (VIDD) and prolong ventilator weaning and hospital length of stay. Intraoperative phrenic nerve stimulation may preserve diaphragm force production to offset VIDD; we also investigated changes in mitochondrial function after stimulation. During cardiothoracic surgeries (n = 21), supramaximal, unilateral phrenic nerve stimulation was performed every 30 min for 1 min. Diaphragm biopsies were collected after the last stimulation and analyzed for mitochondrial respiration in permeabilized fibers and protein expression and enzymatic activity of biomarkers of oxidative stress and mitophagy. Patients received, on average, 6.2 ± 1.9 stimulation bouts. Stimulated hemidiaphragms showed lower leak respiration, maximum electron transport system (ETS) capacities, oxidative phosphorylation (OXPHOS), and spare capacity compared with unstimulated sides. There were no significant differences between mitochondrial enzyme activities and oxidative stress and mitophagy protein expression levels. Intraoperative phrenic nerve electrical stimulation led to an acute decrease of mitochondrial respiration in the stimulated hemidiaphragm, without differences in biomarkers of mitophagy or oxidative stress. Future studies warrant investigating optimal stimulation doses and testing post-operative chronic stimulation effects on weaning from the ventilator and rehabilitation outcomes.